A comparative study of the effect of Furrow irrigation and drip irrigation on some physical soil properties - عطاف, عباده; سوسن هيفا ,; مجد درويش,; ربيع زينة , (Latakia University Journal -Biological Sciences Series, 2024)
The experiment was carried out at the Stakhris Agricultural Research Station in Latakia during the two agricultural seasons 2020-2021, according to a split-plot design, with three replicates for each treatment. The research aimed to study the effect of irrigation method on some physical and chemical soil properties (bulk density (g/cm3), total porosity %, electrical conductivity mm/cm, sodium absorbed percentage SAR, exchangeable sodium percentage ESP%). Two irrigation methods were applied: drip irrigation and furrow irrigation, compared to the experimental soil (control,). The results showed that there were significant differences between the studied treatments, as the bulk density values ​​of the soil decreased when using the drip irrigation method, which reflected positively on the total porosity of the soil, which increased during the research period. The use of the drip irrigation method led to a significant increase in both electrical conductivity, percentage Absorbed sodium, the percentage of exchanged sodium, but it remained within the permissible limits. Based on the above, it can be suggested to use the drip irrigation method, given its tangible role in improving the physical properties of the soil.